If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = 2(3 + -1x) Reorder the terms: 3(2 + x) = 2(3 + -1x) (2 * 3 + x * 3) = 2(3 + -1x) (6 + 3x) = 2(3 + -1x) 6 + 3x = (3 * 2 + -1x * 2) 6 + 3x = (6 + -2x) Add '-6' to each side of the equation. 6 + -6 + 3x = 6 + -6 + -2x Combine like terms: 6 + -6 = 0 0 + 3x = 6 + -6 + -2x 3x = 6 + -6 + -2x Combine like terms: 6 + -6 = 0 3x = 0 + -2x 3x = -2x Solving 3x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3x + 2x = -2x + 2x Combine like terms: 3x + 2x = 5x 5x = -2x + 2x Combine like terms: -2x + 2x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 4(m+1)+7(-m+8)=75 | | 6+3x+3=15 | | y(y-7)-6=2 | | 2x+1+x+4= | | p=3t+2w | | 5n+3n=-12 | | -6(-2v+8)=5(-5v+5)+1 | | 2x-120=180 | | 8d^2+2d= | | -15.00+2.00x=-1 | | 3m-2(m-3)=3 | | 24=3x+6y | | 0.34x+5=9 | | 9x-6-3x=30 | | -5(k-8)+7(-5+k)=-3 | | 2x+10+3x=55 | | 2(u+8)=-6(3u-1)+8u | | 5(4v-5)=5v+4 | | 36=-9(-5+1) | | 8g-3(5+2g)=85-3g | | (3x-4)(7x+5)=0 | | 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 | | 3(5x+4)+12=-8 |